Why Buddhism Is True: The Science and Philosophy of Meditation and Enlightenment - Wright, Robert (Simon & Schuster, 2017)
Intro -- Dedication -- Epigraph -- A Note to Readers -- 1. Taking the Red Pill -- 2. Paradoxes of Meditation -- 3. When Are Feelings Illusions? -- 4. Bliss, Ecstasy, and More Important Reasons to Meditate -- 5. The Alleged Nonexistence of Your Self -- 6. Your CEO Is MIA -- 7. The Mental Modules That Run Your Life -- 8. How Thoughts Think Themselves -- 9. "Self" Control -- 10. Encounters with the Formless -- 11. The Upside of Emptiness -- 12. A Weedless World -- 13. Like, Wow, Everything Is One (at Most) -- 14. Nirvana in a Nutshell -- 15. Is Enlightenment Enlightening? -- 16. Meditation and the Unseen Order -- Appendix A List of Buddhist Truths -- A Note on Terminology -- Acknowledgments -- About the Author -- Notes -- Bibliography -- Index -- Copyright.